2009
DOI: 10.1186/1550-2783-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a pre-exercise, high energy supplement on exercise performance

Abstract: Background: The purpose of this study was to examine the effect of a pre-exercise high energy drink on reaction time and anaerobic power in competitive strength/power athletes. In addition, the effect of the pre-exercise drink on subjective feelings of energy, fatigue, alertness and focus was also explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 31 publications
3
68
3
2
Order By: Relevance
“…Further, the addition of 20 mg of p -synephrine to the PWS supplement used in our study did not appear to provide additive benefit. Results are in agreement with Hoffman et al [71] who reported a significantly greater feeling of energy and focus compared to placebo after ingesting a supplement containing a PWS but contrast those of Gonzales and associates [72] who reported no significant difference in VAS ratings of energy when ingesting a supplement containing caffeine, creatine, β-alanine. However, the participants in that study were administered the supplement 10-min before performing resistance-exercise which may have limited results since it takes about an hour for caffeine levels in the blood to peak after caffeine ingestion [1, 4].…”
Section: Discussionsupporting
confidence: 91%
“…Further, the addition of 20 mg of p -synephrine to the PWS supplement used in our study did not appear to provide additive benefit. Results are in agreement with Hoffman et al [71] who reported a significantly greater feeling of energy and focus compared to placebo after ingesting a supplement containing a PWS but contrast those of Gonzales and associates [72] who reported no significant difference in VAS ratings of energy when ingesting a supplement containing caffeine, creatine, β-alanine. However, the participants in that study were administered the supplement 10-min before performing resistance-exercise which may have limited results since it takes about an hour for caffeine levels in the blood to peak after caffeine ingestion [1, 4].…”
Section: Discussionsupporting
confidence: 91%
“…This could possibly be attributed to the increased production of carnosine from the beta-alanine within the SUP, which in past research has shown to help buffer the hydrogen ions from the lactic acid [29]. However, lactate levels showed no statistical significances between the treatments for any of the time points recorded.…”
Section: Discussionmentioning
confidence: 41%
“…These authors found that ∼1 mg of caffeine per kg of body weight (one 250-mL serving of an energy drink) improved reaction time, alertness and aerobic and anaerobic performance. In contrast, subsequent investigations using energy drinks have shown that ∼1 mg/kg of caffeine is not enough to enhance maximal oxygen uptake [11], peak power during three repetitions of the Wingate test [12], [13] or running velocity during 24 “all-out” sprints [14]. In addition, the ingestion of ∼2 mg/kg of caffeine in the form of an energy drink was ergogenic during a cycling time trial [15] but did not prolong time-to-exhaustion during a running test at 80% VO 2max [16].…”
Section: Introductionmentioning
confidence: 93%